The Counter-Stereotypical Representation of Latinas in the American Police Procedural Comedy Series Brooklyn Nine-Nine (Fox & NBC, 2013-2021) - Putri, Naily Ananda; Primasita, Fitria Akhmerti (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
The representation of Latinas in America has always been stapled with stereotypical traits since their initial appearance in the mainstream media because the representation is depicted from the point of view of Anglo-Americans. It is then intriguing to analyze the representation of Latinas in the American police procedural comedy series Brooklyn Nine-Nine which its Anglo-American producers claimed to be counter-stereotypical to the existing Latina representation in the American mainstream media. Using Roland Barthes' Semiotics, the analysis shows that these characters defy traditional roles by being depicted as competent, assertive professionals with legal citizenship. The findings show that these characters defy traditional roles by being depicted as competent, assertive professionals with legal citizenship. They also diverge from sexualized stereotypes through their portrayal as authoritative figures, avoiding overly sexualized tropes in speech and attire. This portrayal offers a counter-narrative to existing media stereotypes of Latina women.